Nahdlatul Ulama University and Nahdlatul Wathan towards Well Being Islamic Boarding Schools in West Nusa Tenggara - Mukminin, Emha Zainul (YASIN, 2025)
Psychological well-being of santri is a crucial variable in supporting their overall well-being, educational success, and character development within the pesantren environment. The purpose of this study is to explore the diversity of Nahdlatul Ulama and Nahdlatul Wathan in relation to the psychological well-being of their santri. This research employs a descriptive quantitative method with a cross- sectional approach to assess the psychological well-being of students in both Nahdlatul Ulama and Nahdlatul Wathan pesantren. The population of this study, male and female students, with the sample comprising 334 santri using a saturated sampling technique. Data analysis was conducted using comparative tests with SPSS and Structural Equation Modeling (SEM) with AMOS to identify the aspects contributing positively to psychological well-being. The results reveal challenges such as academic pressure, lack of social support, interpersonal conflicts, and limited access to mental health services. An integrated approach is recommended to create a pesantren environment that fosters psychological well-being, enabling santri to thrive in various aspects of life.